Protecting the Paradox of Interprofessional Collaboration. Issue 3 (April 2017) - Huq, Jo-Louise; Reay, Trish; Chreim, Samia
We studied an interprofessional collaboration to understand how professionals engaged with paradox in collective decision-making. At the beginning of our study, we observed vicious cycles in which conflict led to negative tension. Professionals were holding tightly to a particular pole of the paradox, and the higher-status pole was consistently overrepresented in collective decision-making. By the end of our study we observed the presence of virtuous cycles, where conflict led to more positive tension, and where professionals engaged in collective decision-making with more equal representation of conflicting approaches. We call this change process protecting the paradox and we identify three strategies that support this process: (1) promoting equality of both poles, (2) strengthening the weaker pole, and (3) looking beyond the paradox by focusing on desired outcomes. We contribute to the paradox literature by showing how vicious cycles can be shifted to virtuous cycles, how professionals and managers can work together to protect a paradox, and how status differences between poles can be redistributed.